Human amplification of climate-induced greenhouse gas emissions from global small water bodies - Xuliang Zhuang; Xiaoxuan Liu; Shengjun Xu; Xu Wang; Aamer Ali Shah; Lei Wang; Shanghua Wu; Cancan Jiang; Zhiyun Ouyang; Shilong Piao (Proceedings of the National Academy of Sciences, 2026)
Human activities amplify climate-induced greenhouse gas emissions from small water bodies (SWBs), creating critical but unquantified feedback in the global carbon cycle. Here, by training machine learning models on 470 field observations and upscaling to a global database of 3.28 million water bodies, we quantify this human amplification, which drives SWBs to emit 84.5 Tg CO 2 y −1 and 11.0 Tg CH 4 y −1 , a disproportionate share of total inland water emissions (15% of CO 2 and 28% of CH 4 ) from only 6% of Earth’s surface area. This amplification is primarily fueled by agricultural nutrient loading and land use intensity, which elevate CH 4 fluxes in agricultural catchments five times higher than those in forested systems. Future projections show this synergy will increase emissions by up to 30% (CO 2 ) and 14% (CH 4 ) by 2100 under SSP5-8.5, whereas sustainable pathways (SSP1-2.6) could mitigate this emission acceleration through nutrient mitigation efforts, a largely neglected feedback process in current climate change assessments.